High-temperature stable catalyst for CH4 oxidation and preparation method thereof

By introducing NiO on the SiO2 nanosphere support and loading Pd nanoparticles, SiO2-NiO-Pd catalyst is formed. The strong metal-support interaction of Ni-Pd is used to solve the problem of sintering of palladium catalysts at high temperatures, achieving high temperature stability and long-term high-efficiency catalytic performance.

CN119838610AActive Publication Date: 2025-04-18KUNMING UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510054237.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The precious metal palladium (Pd) catalyst is prone to sintering and aggregation under high temperature conditions, resulting in a reduction in catalytic activity and shortening of service life. How to improve its high temperature stability and recycling performance has become a technical problem that needs to be solved urgently.

Method used

SiO2 nanospheres are used as support, and transition metal Ni is introduced through impregnation method to form a SiO2-NiO composite support, and Pd nanoparticles are loaded on its surface to form a SiO2-NiO-Pd high-temperature stabilization catalyst. The strong metal-support interaction (SMSI) between Ni-Pd is used to prevent the sintering and inactivation of Pd particles.

Benefits of technology

It significantly improves the anti-sintering capacity and activity of the catalyst, improves the performance of complete oxidation of methane, and maintains high stability and activity under high temperature conditions, and can maintain high-efficiency performance in a long-term high-temperature operating environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838610A_ABST
    Figure CN119838610A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature stable catalyst for CH4 oxidation and a preparation method thereof, and belongs to the technical field of catalysts.The preparation method comprises the following steps that SiO2 nanospheres serve as a matrix, transition metal Ni is introduced through an impregnation method, and a core-shell structure composite carrier SiO2-NiO with the surface evenly covered with a thin layer NiO is formed; then Pd is loaded on the composite carrier SiO2-NiO through an impregnation method, and the loaded palladium-based catalyst SiO2-NiO-Pd, namely the high-temperature stable catalyst, is obtained. The catalyst can be used for high-temperature methane catalytic combustion reaction and has excellent catalytic activity, and the methane conversion rate can reach 100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a high-temperature stable catalyst for CH4 oxidation and a preparation method thereof. Background Art

[0002] With the continuous increase in energy demand and increasingly stringent environmental protection requirements, methane (CH4), as a clean and efficient energy source with abundant reserves, has gradually become an important alternative to traditional fossil fuels. However, if methane is not completely burned during the combustion process, it will produce a variety of pollutants including carbon monoxide (CO), volatile organic compounds (VOCs) and fine particulate matter (PM2.5), causing serious environmental problems. At the same time, incomplete combustion will reduce energy utilization efficiency and limit the further promotion of methane as a clean energy source. Therefore, the development of efficient catalysts that can achieve complete oxidation of methane has become an important research direction in the current energy field.

[0003] Catalysts used for methane oxidation are mainly divided into two categories, namely precious metal catalysts and non-precious metal catalysts. Studies have shown that precious metal palladium (Pd) catalysts have been widely studied and applied due to their high activity in the complete oxidation of methane. However, since Pd nanoparticles are prone to sintering and aggregation under high temperature conditions, resulting in reduced catalytic activity and shortened service life, how to improve their high temperature stability and recycling performance has become a technical problem that needs to be solved urgently. By rationally designing catalyst carriers, such as introducing porous structures, high specific surface areas, and introducing transition metals to form strong metal-support interactions (SMSI) with Pd particles, the sintering resistance and activity of the catalyst can be significantly improved. Therefore, the development of a new composite carrier based on SiO2 nanospheres combined with transition metal nickel (Ni) provides a new research direction and technical path for improving the performance of palladium-based methane catalysts.

[0004] Among the many factors that affect the performance of methane catalytic combustion, the particle size of precious metals is considered to be one of the most important factors. Usually, the particle size affects the dispersion of precious metals on the carrier, their own valence state and coordination number, and thus affects the reaction. Among them, silica (SiO2) carriers have become one of the hot spots in the current research of Pd-based catalytic carriers due to their unique structure and surface properties. The surface hydroxyl groups of SiO2 can interact with Pd nanoparticles, thereby enhancing their dispersion and stability. This interaction not only prevents the aggregation of particles, but also improves the mechanical strength of the catalyst. In the paper (Enhanced Thermal Stability of Palladium Catalysts on Mesoporous Silica for Methane Combustion.), the authors pointed out in the study that mesoporous SiO2 carriers can significantly improve the thermal stability and methane catalytic performance of Pd nanoparticles. Its unique mesoporous structure allows rapid mass transfer of reactants and products in the pores, thereby improving the overall reaction efficiency. However, mesoporous SiO2 may collapse its pore structure under high temperature conditions (>800℃), resulting in a significant decrease in specific surface area, further leading to the agglomeration and deactivation of Pd. At the same time, since SiO2 is relatively inert in an oxidizing environment and lacks oxygen vacancies, it cannot provide additional redox capacity for Pd, resulting in a reduction in Pd active sites and a decrease in catalytic activity. In addition, in the paper (Systematic Identification of Promoters for Methane Oxidation Catalysts Using Size and Composition Controlled Pd-Based Bimetallic Nanocrystals), the authors introduced a series of transition metals (M = V, Mn, Fe, Co, Ni, Zn, Sn) on the Al2O3 support to investigate their effects on the performance of the methane catalytic oxidation reaction. The study found that the Pd-Ni / Al2O3 catalyst had the greatest increase in the decomposition temperature of PdO. This effect indicates that due to the strong interaction between Pd and NiO, NiO significantly improves the overall thermal stability and sintering resistance of the catalyst by enhancing the thermal stability of the PdO active phase. However, the acidity of Al2O3 may cause the Pd and NiO particles to agglomerate at high temperatures, reducing the activity of the catalyst. Summary of the invention

[0005] Based on the above research background, the present invention proposes a high temperature stable catalyst for CH4 oxidation and its preparation method. The present invention uses SiO2 as a carrier and combines the strong metal-support interaction (SMSI) of NiO with a Pd-based catalyst to improve the performance of the catalyst in the complete oxidation of methane by optimizing particle dispersibility, enhancing the thermal stability of the active phase and inhibiting sintering.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing a high temperature stable catalyst, comprising the following steps:

[0008] Taking SiO2 nanospheres as the matrix, transition metal Ni is introduced by impregnation method to form a core-shell structure composite carrier SiO2-NiO with a thin layer of NiO uniformly covered on the surface; then Pd is loaded on the composite carrier SiO2-NiO by impregnation method to obtain a loaded palladium-based catalyst SiO2-NiO-Pd, that is, a high-temperature stable catalyst.

[0009] The inertness of SiO2 material can ensure that it maintains stability at high operating temperatures, and SiO2 has strong metal-support interaction (SMSI), which can become a suitable catalyst support. The present invention adopts impregnation method to introduce transition metal nickel, and prepares SiO2-NiO composite support, Ni oxide promotes catalyst thermal stability by increasing the thermal stability of active PdO phase, and by strong metal-support interaction (SMSI) between Ni-Pd, sintering and deactivation of Pd particles at high temperature are effectively prevented. Then Pd nanoparticles are loaded on SiO2-NiO composite support by impregnation method, forming SiO2-NiO-Pd high temperature stable catalyst, and the NiO layer uniformly distributed on the surface of SiO2-NiO support provides an ideal anchoring point for the loading of Pd nanoparticles, significantly improving the catalytic activity and stability of Pd.

[0010] Furthermore, the SiO2 nanospheres are The method comprises the following steps: mixing 25-28 wt% ammonia water, anhydrous ethanol and deionized water, stirring, then adding tetraethyl orthosilicate, continuing stirring, centrifuging, and drying to obtain SiO2 nanospheres;

[0011] The volume ratio of the ammonia water with a concentration of 25-28wt%, anhydrous ethanol, deionized water and tetraethyl orthosilicate is (200-250): (200-250): (10-20): (20-30).

[0012] Furthermore, the specific preparation steps of the composite carrier SiO2-NiO include: mixing SiO2 nanospheres with deionized water, adding a nickel source, adjusting the pH to 6-7, and stirring until the water evaporates to obtain the composite carrier SiO2-NiO;

[0013] Wherein, the dosage ratio of the SiO2 nanospheres to deionized water is (100-110) g: 250 mL;

[0014] The mass ratio of the SiO2 nanospheres to the nickel source is (100-110):(10-11), and the nickel source is nickel acetate.

[0015] Furthermore, the SiO2-NiO-Pd includes fresh SiO2-NiO-Pd-F and aged SiO2-NiO-Pd-A.

[0016] The SiO2-NiO-Pd high temperature stable catalyst doped with NiO can effectively reduce the ignition temperature of methane.

[0017] Furthermore, the specific preparation steps of the fresh SiO2-NiO-Pd-F include: mixing the composite carrier SiO2-NiO with deionized water, stirring, adding a palladium source, adjusting the pH to 5-6, stirring until the water evaporates and then drying, and calcining at a first temperature to obtain fresh SiO2-NiO-Pd-F;

[0018] The specific preparation steps of the aged SiO2-NiO-Pd-A include: continuing to calcine the fresh SiO2-NiO-Pd-F at a second temperature to obtain aged SiO2-NiO-Pd-A; the second temperature is 180-320°C higher than the first temperature.

[0019] Furthermore, the amount of the palladium source added is 1% of the mass of the composite carrier SiO2-NiO; and / or

[0020] The drying conditions are: drying at 120°C for 12h; and / or

[0021] The calcination conditions are: calcination at 550-570°C for 3h; and / or

[0022] The conditions for continued calcination are: calcination at 850-870°C for 25h.

[0023] The second object of the present invention is to provide a high temperature stable catalyst prepared by the above preparation method. The obtained catalyst exhibits excellent high temperature stability and methane catalytic oxidation performance.

[0024] The third purpose of the present invention is to provide an application of the above-mentioned high-temperature stable catalyst in the complete oxidation reaction of CH4, which can be widely used in high-efficiency catalytic systems in the field of clean energy, and is particularly suitable for long-term high-temperature operation environments. It provides a new catalyst design scheme for low-carbon energy transformation and has broad industrial application prospects.

[0025] A fourth object of the present invention is to provide an application of the above-mentioned high-temperature stable catalyst in an efficient catalytic system in the field of clean energy.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects:

[0027] The present invention successfully developed a catalyst with both high catalytic activity and high-temperature thermal stability. The catalyst described in the present invention not only meets the actual needs of clean energy utilization and low-carbon transformation, but also provides a new idea for improving the thermal stability of Pd catalysts in methane catalytic combustion reactions.

[0028] The SiO2-doped Ni-supported palladium catalyst for methane catalytic combustion prepared by the present invention can be used for high-temperature methane catalytic combustion reaction and has outstanding catalytic activity, and the methane conversion rate can reach 100%. The catalyst shows excellent stability during the continuous combustion reaction process, that is, after 5 consecutive uses, it can still maintain 100% of the catalytic effect.

[0029] The catalyst prepared by the invention has a simple preparation process, can be recycled for a long time, and has good practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 The catalysts in Example 1 and Comparative Example 1 were heated at 40000 mL min -1 ·g -1 Performance comparison chart under the same gas flow rate conditions;

[0032] Figure 2 The results are as follows: the different catalysts in Example 1 and Comparative Example 1 under the same conditions and different gas flow rates (40000 mL·min -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 ) performance comparison chart;

[0033] Figure 3 The SiO2-NiO-Pd catalyst prepared in Example 1 was heated to 40000 mL·min -1 ·g -1 Performance diagram of the next cycle test with 5 reactions;

[0034] Figure 4 TEM images and EDX images of SiO2-NiO-Pd catalysts; (a) is a TEM image and EDX image of SiO2-NiO-Pd-F catalyst; (b) is a TEM image and EDX image of SiO2-NiO-Pd-A catalyst;

[0035] Figure 5 TEM images and EDX images of SiO2-Pd catalysts; (a) is a TEM image and EDX image of SiO2-Pd-F catalysts; (b) is a TEM image and EDX image of SiO2-Pd-A catalysts;

[0036] Figure 6 XRD patterns of different catalysts in Example 1 and Comparative Example 1; wherein a is SiO2-Pd catalyst; b is SiO2-NiO-Pd catalyst;

[0037] Figure 7 Thermogravimetric curve of the SiO2-NiO-Pd catalyst prepared in Example 1; wherein a is the SiO2-NiO-Pd-F catalyst; b is the SiO2-NiO-Pd-A catalyst;

[0038] Figure 8 The thermogravimetric curve of the SiO2-Pd catalyst prepared in Comparative Example 1; wherein a is the SiO2-Pd-F catalyst; b is the SiO2-Pd-A catalyst;

[0039] Fig. 9 The catalysts in Example 1 and Comparative Example 2 were heated at 40000 mL min -1 ·g -1 Performance comparison chart under the same gas flow rate conditions;

[0040] Fig.10 The results are as follows: the different catalysts in Example 1 and Comparative Example 2 under the same conditions and different gas flow rates (40000 mL·min -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 ) performance comparison chart;

[0041] Fig.11TEM images and EDX images of NiSiO3-Pd catalyst; (a) is the TEM image and EDX image of NiSiO3-Pd-F catalyst; (b) is the TEM image and EDX image of NiSiO3-Pd-A catalyst;

[0042] Fig.12 XRD patterns of different catalysts in Example 1 and Comparative Example 2; wherein a is SiO2-NiO-Pd catalyst; b is NiSiO3-Pd catalyst;

[0043] Fig.13 The thermogravimetric curve of the NiSiO3-Pd catalyst prepared in Comparative Example 2; wherein a is the NiSiO3-Pd-F catalyst; b is the NiSiO3-Pd-A catalyst. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] The present invention provides a high temperature stable catalyst, comprising a SiO2 carrier, Pd loaded on the carrier, and a doped transition metal Ni. The main method comprises: S1, under the condition of using anhydrous ethanol and deionized water as solvents, using ammonia water (mass concentration of 25-28%) as an alkaline catalyst, and tetraethyl orthosilicate (TEOs) as a silicon source, by The method comprises the following steps: S2, adding a nickel acetate solution as a Ni precursor to the SiO2 matrix, loading Ni onto the SiO2 matrix by a conventional impregnation method, reacting until the water content of the solution evaporates and drying, and obtaining a SiO2-NiO composite carrier; S3, adding a Pd(NO3)2 solution as a Pd precursor to the SiO2-NiO composite carrier, loading Pd onto the SiO2-NiO carrier by a conventional impregnation method, reacting until the water content of the solution evaporates and drying, and obtaining a palladium-loaded catalyst precursor SiO2-NiO-Pd; S4, calcining the precursor SiO2-NiO-Pd in ​​S3 in a muffle furnace to obtain a fresh catalyst (SiO2-NiO-Pd-F); S5, continuing to calcine the SiO2-NiO-Pd-F in S4 in a muffle furnace to obtain an aged catalyst (SiO2-NiO-Pd-A).

[0050] The present invention uses stable SiO2 as a carrier, introduces an additive Ni to improve the surface characteristics of the carrier, forms a SiO2-NiO composite carrier, and finally forms a SiO2-NiO-Pd catalyst. Doping with transition metal nickel (Ni) can inhibit the decomposition of PdO particles, improve the thermal stability of the active phase, thereby improving the catalytic activity and thermal stability of the catalyst. At the same time, the composite material doped with Ni as a carrier can effectively reduce the methane ignition temperature. The good dispersion of Ni on the SiO2 surface not only enhances the mechanical stability of the carrier, but also may produce a synergistic catalytic effect with Pd in ​​methane oxidation.

[0051] The specific technical solution includes the following steps:

[0052] (1) Preparation of SiO2 nanospheres: Ammonia water, anhydrous ethanol and deionized water with a concentration of 25-28 wt% are mixed and stirred, and then tetraethyl orthosilicate is added, and the mixture is stirred continuously, centrifuged and dried to obtain SiO2 nanospheres;

[0053] (2) Preparation of composite carrier SiO2-NiO: SiO2 nanospheres are mixed with deionized water, a nickel source is added, the pH is adjusted to 6-7, the mixture is stirred until the water evaporates, and then dried to obtain a composite carrier SiO2-NiO;

[0054] (3) Preparation of fresh SiO2-NiO-Pd-F: The composite carrier SiO2-NiO is mixed with deionized water, stirred, a palladium source is added, and the pH is adjusted to 5-6. The mixture is stirred until the water evaporates, dried, and calcined to obtain fresh SiO2-NiO-Pd-F.

[0055] (4) Preparation of aged SiO2-NiO-Pd-A: The composite carrier SiO2-NiO is mixed with deionized water, stirred, a palladium source is added, and the pH is adjusted to 5-6. The mixture is stirred until the water evaporates, dried, and calcined to obtain fresh SiO2-NiO-Pd-F. The fresh SiO2-NiO-Pd-F is further calcined to obtain aged SiO2-NiO-Pd-A.

[0056] In some embodiments of the present invention, the volume ratio of the ammonia water with a concentration of 25-28wt%, anhydrous ethanol, deionized water and tetraethyl orthosilicate in step (1) is (200-250): (200-250): (10-20): (20-30). Exemplarily, in the following preferred embodiments of the present invention, the volume ratio of the ammonia water with a concentration of 25-28wt%, anhydrous ethanol, deionized water and tetraethyl orthosilicate is 245: 225: 10: 21 or any range between the aforementioned ratios.

[0057] In some embodiments of the present invention, the ratio of the amount of SiO2 nanospheres to deionized water in step (2) is (100-110) g: 250 mL. Exemplarily, in the following preferred embodiments of the present invention, the ratio of the amount of SiO2 nanospheres to deionized water is 100 g: 250 mL or any range between the aforementioned ratios.

[0058] In some embodiments of the present invention, the mass ratio of the SiO2 nanospheres to the nickel source in step (2) is (100-110): (10-11), and the nickel source is a nickel acetate solution with a mass concentration of 10wt%. Exemplarily, in the following preferred embodiments of the present invention, the mass ratio of the SiO2 nanospheres to the nickel source is 100: 10 or any range between the aforementioned ratios.

[0059] In some embodiments of the present invention, in step (2), the stirring temperature is 70-80°C; illustratively, in the following preferred embodiments of the present invention, the stirring temperature is 70°C or any value between the aforementioned ranges. The drying temperature is 100-120°C; illustratively, in the following preferred embodiments of the present invention, the drying temperature is 120°C or any value between the aforementioned ranges.

[0060] In some embodiments of the present invention, the amount of the palladium source added in step (3) is 1 wt% of the mass of the composite carrier SiO2-NiO, and the palladium source is a palladium nitrate solution with a mass concentration of 24 wt%.

[0061] In some embodiments of the present invention, in step (3), the stirring temperature is 70-80°C; illustratively, in the following preferred embodiments of the present invention, the stirring temperature is 70°C or any value between the aforementioned ranges. The drying temperature is 100-120°C; illustratively, in the following preferred embodiments of the present invention, the drying temperature is 120°C or any value between the aforementioned ranges.

[0062] In some embodiments of the present invention, the calcination temperature in step (3) is 550-570°C, and the calcination time is 3 hours. Exemplarily, in the following preferred embodiments of the present invention, the calcination temperature is 550°C or any value between the aforementioned ranges.

[0063] In some embodiments of the present invention, the temperature of the continued calcination in step (4) is 850-870°C and the time of the continued calcination is 25h. Exemplarily, in the following preferred embodiments of the present invention, the temperature of the continued calcination is 850°C or any value between the aforementioned ranges.

[0064] The high temperature stable catalyst is prepared by the above preparation method.

[0065] The application of the high-temperature stable catalyst in the complete oxidation reaction of CH4 can be widely used in high-efficiency catalytic systems in the field of clean energy, and is particularly suitable for long-term high-temperature operation environments. It provides a new catalyst design scheme for low-carbon energy transformation and has broad industrial application prospects.

[0066] The activity test of the catalyst prepared by the present invention is carried out, and the reaction gas is a standard gas composed of CH4, O2 and N2, which passes through a mass flowmeter and a flow display. The catalyst activity test is carried out in a quartz tube fixed bed reactor, the inner diameter of the quartz tube is 6mm, and the length is 310mm. The catalyst is placed in a constant temperature zone in the reaction tube, fixed on both sides with quartz wool, heated by an electric furnace, and a thermocouple is inserted into the furnace wall for temperature testing and control. The specific test method is: the catalyst is pressed, ground and screened, and 40-60 mesh particles are selected for activity evaluation. The test method is: 0.5g of the catalyst is loaded into a stainless steel reactor with an inner diameter of 5mm, and after the reaction gas is introduced to equilibrium, the catalyst is pretreated from 100°C to 550°C at a heating rate of 20°C / min, cooled to 100°C and then heated to 550°C again for CH4 oxidation. The reaction gas composition is 5000ppm CH4, 6000ppm O2, with N2 as the balance gas, and the total gas flow rate is 40000-80000mL·min-1 ·g -1 The gas composition and content were detected online using the American Andover MKS multi-gas series FTIR gas analyzer.

[0067] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0068] The raw materials used in the present invention are all purchased from the market.

[0069] The technical solution of the present invention is further illustrated by the following embodiments.

[0070] Example 1

[0071] A high temperature stable catalyst comprises the following steps:

[0072] (1) Preparation of SiO2 nanospheres: 245 mL of ammonia water was mixed with 225 mL of anhydrous ethanol and 10 mL of deionized water, and stirred at room temperature for 30 min until the solution was uniformly mixed. Then, 21 mL of ethyl orthosilicate was added dropwise (the addition was completed within 2 min), and stirred at room temperature for 4 h. The white product was separated by centrifugation, and then transferred to a blower and dried at 120°C for 12 h to obtain SiO2 nanospheres.

[0073] (2) Preparation of composite carrier SiO2-NiO: 200 g of SiO2 nanospheres were dissolved in 500 mL of deionized water, and stirred until SiO2 was completely dissolved without precipitation. 20 g of nickel acetate solution with a mass concentration of 10 wt% was added, and the pH was adjusted to 7 with ammonia water. The solution was heated to 70° C. and stirred continuously until the water evaporated. The resultant was placed in an oven at 120° C. and dried for 12 h to obtain a composite carrier SiO2-NiO;

[0074] (3) Preparation of fresh SiO2-NiO-Pd-F: 100 g of the composite carrier SiO2-NiO was dissolved in 500 mL of deionized water until the composite carrier SiO2-NiO was completely dissolved without precipitation, 0.42 g of a 24 wt% palladium nitrate solution was added, the pH was adjusted to 6 with acetic acid and ammonia water, the solution was heated to 70°C and stirred continuously until the water in the solution evaporated, the resultant was placed in an oven at 120°C and dried for 12 h to obtain a SiO2-NiO-Pd catalyst precursor; the obtained SiO2-NiO-Pd catalyst precursor was calcined in a muffle furnace at 550°C for 3 h to obtain a fresh SiO2-NiO-Pd-F;

[0075] (4) Preparation of aged SiO2-NiO-Pd-A: The prepared fresh SiO2-NiO-Pd-F was further calcined at 850°C in a muffle furnace for 25 h to obtain aged SiO2-NiO-Pd-A.

[0076] Comparative Example 1

[0077] A high temperature stable catalyst comprises the following steps:

[0078] (1) Preparation of SiO2 nanospheres: 245 mL of ammonia water was mixed with 225 mL of anhydrous ethanol and 10 mL of deionized water, and stirred at room temperature for 30 min until the solution was uniformly mixed. Then, 21 mL of ethyl orthosilicate was added dropwise (the addition was completed within 2 min), and stirred at room temperature for 4 h. The white product was separated by centrifugation, and then transferred to a blower and dried at 120°C for 12 h to obtain SiO2 nanospheres.

[0079] (2) Preparation of SiO2-Pd precursor: 100 g of SiO2 nanospheres were dissolved in 500 mL of deionized water, and stirred until SiO2 was completely dissolved without precipitation, then 0.42 g of 24 wt% palladium nitrate solution was added, and the pH was adjusted to 6 with acetic acid and ammonia water. The solution was heated to 70°C and stirred continuously until the water in the solution evaporated. The resultant was placed in an oven and dried at 120°C for 12 h to obtain a SiO2-Pd precursor.

[0080] (3) Preparation of SiO2-Pd-F: The SiO2-Pd precursor was calcined in a muffle furnace at 550°C for 3 h to obtain a fresh SiO2-Pd-F catalyst;

[0081] (4) Preparation of aged SiO2-Pd-A: The prepared fresh SiO2-Pd-F catalyst was further calcined at 850°C in a muffle furnace for 25 h to obtain an aged SiO2-Pd-A catalyst.

[0082] Application Example 1

[0083] 1. Effect of catalyst on methane conversion rate

[0084] 0.5 g of the catalyst prepared in Example 1 and Comparative Example 1 were respectively placed in the constant temperature zone of the fixed bed reactor quartz tube, fixed on both sides with quartz wool, and heated by an electric furnace. The reaction gas was introduced in the above manner, with a specific composition of 5000 ppm CH4, 6000 ppm O2, with N2 as the balance gas, and the total gas flow rate was 40000 mL min -1 ·g -1 The reaction temperature was controlled to be between 100 and 550 °C. The gas composition and content were detected online using the American Andover MKS multi-gas series FTIR gas analyzer. The CH4 conversion rate X can be calculated by formula (1):

[0085]

[0086] Figure 1 The catalysts in Example 1 and Comparative Example 1 were heated at 40000 mL min-1 ·g -1 (abbreviated as 4W in the figure, the same below) Performance comparison chart under the same gas flow rate conditions, investigating the effect of different catalysts on methane conversion rate. The results show that the maximum methane conversion efficiency of SiO2-Pd-F catalyst is less than 80%, and the maximum methane conversion efficiency of SiO2-Pd-A catalyst after aging treatment is even less than 50%. The methane conversion rate of SiO2-NiO-Pd-F catalyst doped with transition metal Ni can reach 100%, and the methane conversion rate of SiO2-NiO-Pd-A catalyst after aging treatment can still reach 98%. The reason is that nickel can be evenly distributed on the surface of silica, which can increase the interaction force with the active phase of PdO. At the same time, the presence of silica helps to improve the stability of nickel and prevent nickel from agglomerating or losing during the reaction process, which enables the catalyst to maintain a good structure and catalytic performance under high temperature conditions of methane combustion.

[0087] 2. Effect of gas flow rate on catalyst methane conversion rate

[0088] 0.5 g of the catalyst prepared in Example 1 and Comparative Example 1 were placed in the constant temperature zone of the fixed bed reactor quartz tube, fixed on both sides with quartz wool, and heated by an electric furnace. The reaction gas was introduced in the above manner, with a specific composition of 5000 ppm CH4, 6000 ppm O2, and N2 as the balance gas, with a total gas flow rate of 40000, 60000, and 80000 mL·min, respectively. -1 ·g -1 The reaction temperature was controlled to be in the range of 100-550°C. The gas composition and content were detected online using the American Andover MKS multi-gas series FTIR gas analyzer.

[0089] Figure 2 The results are as follows: the different catalysts in Example 1 and Comparative Example 1 under the same conditions and different gas flow rates (40000 mL·min -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 ) performance comparison chart, and investigated the effect of different gas flow rates on the methane conversion rate of the catalyst. The results showed that the gas flow rate had a great influence on the performance of the SiO2-Pd catalyst, and the ignition temperature increased with the increase of gas flow rate (40000mL·min -1 ·g -1 <60000mL·min -1 ·g -1 <80000mL·min -1 ·g -1). This shows that as the gas flow rate increases, the contact time between methane and the catalyst surface shortens, which is not conducive to the methane oxidation reaction at low temperatures. The gas flow rate has little effect on the performance of the SiO2-NiO-Pd-F catalyst with strong catalytic activity. Although the ignition temperature also increases slightly with the increase in flow rate, the overall ignition temperature is significantly lower than that of the SiO2-Pd-F catalyst. The methane conversion rate of the SiO2-NiO-Pd-F catalyst is 40000mL·min at different gas flow rates. -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 The results show that the rational design of the catalyst carrier (introduction of NiO) can effectively improve the adaptability and performance stability of the catalyst at different gas flow rates, providing an important reference for the practical industrial application of methane catalytic oxidation.

[0090] 3. Catalyst used for methane catalytic combustion cycle stability test

[0091] 0.5 g of the SiO2-NiO-Pd catalyst prepared in Example 1 was placed in the constant temperature zone of the fixed bed reactor quartz tube, fixed on both sides with quartz wool, and heated by an electric furnace. The reaction gas was introduced in the above manner, with a specific composition of 5000 ppm CH4, 6000 ppm O2, with N2 as the balance gas, and the total gas flow rate was 40000 mL min -1 ·g -1 The reaction temperature was controlled to be between 100 and 550 °C. The gas composition and content were detected online using the American Andover MKS multi-gas series FTIR gas analyzer. After the first round of testing, the heating was stopped and the catalyst was allowed to cool naturally to room temperature. After the temperature stabilized, a new round of catalytic activity evaluation was conducted under the same conditions as the first test to ensure the consistency and comparability of subsequent tests. The test was repeated 5 times to determine the stability of the catalyst.

[0092] Figure 3 The SiO2-NiO-Pd catalyst prepared in Example 1 was heated to 40000 mL·min -1 ·g -1The performance graph of the 5-cycle test was used to investigate the cyclic stability test of SiO2-NiO-Pd catalyst for methane catalytic combustion. The results showed that under the test conditions, the catalyst needs to withstand high-temperature oxidation reactions. The performance remained consistent after 5 cycles, indicating that the structural stability of the SiO2-NiO carrier and the dispersion of the Pd particles were not damaged. The SiO2-NiO-Pd catalyst was stable at a total gas flow rate of 40000mL min -1 ·g -1 In the five cycle tests under the conditions, the methane conversion rate can reach 100% and remain stable after the complete conversion temperature, which shows that the active sites of the catalyst are not deactivated by high temperature or long-term use during the cycle. This stability is mainly attributed to the uniform distribution of the NiO layer and the strong metal-support interaction between it and the Pd particles, which provides reliable technical support for the realization of efficient methane catalytic combustion and demonstrates its great potential in practical industrial applications, especially in the fields of clean energy utilization and industrial waste gas treatment under long-term, high-flow and high-temperature conditions.

[0093] 4. Catalyst structure and stability characterization

[0094] 1) The SiO2-NiO-Pd catalyst prepared in Example 1 was characterized. Figure 4 The TEM and EDX images of the SiO2-NiO-Pd catalyst show that the SiO2 carrier in the fresh SiO2-NiO-Pd-F catalyst still presents a complete spherical structure with a relatively smooth surface, providing good support for Pd and NiO. The NiO and Pd on the surface of the SiO2 carrier are evenly distributed, and there is no significant aggregation of particles. The spherical structure of the SiO2 carrier in the aged SiO2-NiO-Pd-A catalyst remains intact, but the surface may be slightly rough or collapsed due to high temperature. High-temperature calcination leads to partial reconstruction of the NiO layer, weakening its anchoring effect on the Pd particles. The Pd particles sinter under high temperature for a long time, and obvious agglomeration occurs, resulting in uneven distribution of Pd.

[0095] 2) The SiO2-Pd catalyst prepared in Comparative Example 1 was characterized. Figure 5The TEM and EDX images of SiO2-Pd catalysts show that the spherical structure of the SiO2 carrier in the fresh SiO2-Pd-F catalyst is intact, the surface is smooth, and no obvious deformation or cracks are observed. Pd nanoparticles are attached to the SiO2 surface with a small particle size, showing a uniform and dispersed state, with a small particle size and no obvious agglomeration phenomenon, and the active sites are fully exposed. The low temperature calcination condition of 550℃ has little effect on the carrier and active components, which is conducive to maintaining the high dispersibility and surface activity of Pd particles. The spherical structure of the SiO2 carrier of the aged SiO2-Pd-A catalyst remains intact, but the surface is relatively rough, which may be partially shrunk or morphologically changed due to high temperature. High temperature and long-term calcination causes Pd particles to sinter to form large particles, reduce dispersibility, reduce specific surface area, and significantly reduce active sites. High temperature and long-term calcination leads to roughening of the carrier surface and Pd migration, which affects the overall performance of the catalyst, especially reducing the catalytic efficiency in long-term high temperature reactions.

[0096] 3) The SiO2-NiO-Pd catalyst prepared in Example 1 and the SiO2-Pd catalyst prepared in Comparative Example 1 were characterized. Figure a is the XRD curve of the SiO2-Pd catalyst. After the SiO2-Pd-F catalyst was heat-treated at 550°C / 3h, the Pd (111) diffraction peak was weak and wide, indicating that the Pd nanoparticle size was small (corresponding to the particle size distribution). SiO2 exhibited amorphous characteristics (wide background peak), indicating that the carrier did not crystallize after the 550°C / 3h heat treatment. The Pd (111) diffraction peak intensity of the SiO2-Pd-A catalyst was significantly enhanced and narrowed, indicating that the Pd particle size was significantly increased. The amorphous characteristics of SiO2 remained unchanged, indicating that the carrier had good thermal stability, but the anchoring effect on Pd was weakened. Figure b is the XRD curve of SiO2-NiO-Pd catalyst. The diffraction peak intensity of PdO crystals in SiO2-NiO-Pd-F catalyst is weak, indicating that the Pd particles are less crystalline, smaller in size and better in dispersion. After heat treatment at 850℃ / 3h, the Pd diffraction peak of SiO2-NiO-Pd-A catalyst is significantly enhanced, accompanied by a slight shift in the peak position, which may be related to the increase in Pd particle size and the release of surface stress. The NiO diffraction peak is still clear in the aged state, indicating that NiO has good thermal stability at high temperatures and may have played a role in physical isolation and chemical anchoring of Pd particles.

[0097] 4) The SiO2-NiO-Pd catalyst prepared in Example 1 was characterized. Figure 7The thermogravimetric curve of SiO2-NiO-Pd catalyst. It can be seen that the black curve (the black curve represents the mass change of SiO2-NiO-Pd catalyst with temperature / time during the programmed temperature rise process, the same below) and the red curve (the red curve represents the mass change rate of SiO2-NiO-Pd catalyst with temperature / time, and its peak point represents the temperature / time point at which the mass change rate of each sample is the fastest, the same below) have no obvious fluctuations, and the mass loss is very small (from room temperature to 1000℃, the remaining mass of the catalyst is close to 100%, and the mass change rate is less than 2%), indicating that the catalyst has no obvious mass loss fluctuations during the entire heating process. SiO2-NiO-Pd catalyst exhibits excellent thermal stability under both fresh and aged heat treatment conditions.

[0098] 5) The SiO2-Pd catalyst prepared in Comparative Example 1 was characterized. Figure 8 The thermogravimetric curve of the SiO2-Pd catalyst prepared in Comparative Example 1. It can be seen that there is no obvious fluctuation in both the black and red curves, indicating that the catalyst has no obvious mass loss fluctuation during the entire heating process. The SiO2-Pd catalyst exhibits excellent thermal stability under heating conditions.

[0099] It can be seen from the above results that the present invention successfully prepared SiO2-NiO-Pd catalyst doped with transition metal Ni by impregnation method. A series of characterization analyses confirmed that in the uniform NiO layer formed on SiO2, the introduction of NiO not only enhanced the generation of active oxygen species through oxygen vacancies, but also further improved the dispersibility and reactivity of Pd by utilizing the metal-support interaction (SMSI) between Ni and Pd. In addition, the NiO layer anchored the Pd particles to prevent them from migrating and aggregating at high temperatures. Compared with the SiO2-Pd catalyst without Ni doping, at a gas flow rate of 40000mL·min -1 ·g -1 When SiO2-NiO-Pd catalyst has 50 From 486℃ to 386℃, T 90 The cyclic test results show that the SiO2-NiO-Pd catalyst can still maintain a high catalytic effect after 5 consecutive operations.

[0100] Comparative Example 2

[0101] The same as Example 1, except that the preparation method of adding Ni to the composite carrier in step (2) is different to form hollow NiSiO3 nanospheres. The specific technical scheme is as follows:

[0102] A hollow NiSiO3 nanosphere supported catalyst comprises the following steps:

[0103] (1) Preparation of SiO2 nanospheres: 245 mL of ammonia water was mixed with 225 mL of anhydrous ethanol and 10 mL of deionized water, and stirred at room temperature for 30 min until the solution was uniformly mixed. Then, 21 mL of ethyl orthosilicate was added dropwise (the addition was completed within 2 min), and stirred at room temperature for 4 h. The white product was separated by centrifugation, and then transferred to a blower and dried at 120°C for 12 h to obtain SiO2 nanospheres.

[0104] (2) Preparation of hollow NiSiO3 nanospheres: nickel acetate was dissolved in 160 mL of deionized water containing 0.8 g of SiO2 sol particles (nickel acetate was added at a molar ratio of Si to Ni = 1:2, i.e., 6.63 g of nickel acetate), and the resulting mixture was ultrasonically irradiated for 60 min to form a uniform solution (the temperature was controlled in the range of 20-30°C), and the obtained uniform solution was transferred to a stainless steel autoclave, which was sealed and kept at 180°C for 24 h, then air-cooled to room temperature, the resulting precipitate was collected, washed with distilled water, and dried at 120°C for 12 h to obtain a hollow NiSiO3 carrier;

[0105] (3) Preparation of fresh NiSiO3-Pd-F: 100 g of hollow NiSiO3 carrier was dissolved in 500 mL of deionized water until the carrier NiSiO3 was completely dissolved without precipitation, 0.42 g of 24 wt% palladium nitrate solution was added, the pH was adjusted to 6 with acetic acid and ammonia water, the solution was heated to 70°C and stirred continuously until the water in the solution evaporated, and the resultant was placed in an oven at 120°C and dried for 12 h to obtain a NiSiO3-Pd catalyst precursor;

[0106] (4) Preparation of fresh NiSiO3-Pd-F: The obtained NiSiO3-Pd catalyst precursor was calcined in a muffle furnace at 550°C for 3 h to obtain fresh NiSiO3-Pd-F;

[0107] (5) Preparation of aged NiSiO3-Pd-A: The prepared fresh NiSiO3-Pd-F was further calcined at 850°C in a muffle furnace for 25 h to obtain aged NiSiO3-Pd-A.

[0108] Application Example 2

[0109] 1. Effect of catalyst on methane conversion rate

[0110] Take 0.5g of the catalyst prepared in Example 1 and Comparative Example 2 respectively and place it in the constant temperature zone of the quartz tube of the fixed bed reactor, fix it with quartz wool on both sides, and heat it with an electric furnace. Introduce the reaction gas in the above manner, the specific composition is: 5000ppm CH4, 6000ppm O2, N2 is used as the balance gas, and the total gas flow rate is 40000mL·min-1·g-1. Control the reaction temperature range to be 100-550℃. Use the American Andover MKS multi-gas series FTIR gas analyzer to detect the gas composition and content online. The CH4 conversion rate X can be calculated by formula (1):

[0111]

[0112] Fig. 9 The catalysts in Example 1 and Comparative Example 2 were heated to 40000 mL·min-1·g -1 (Abbreviated as 4W in the figure, the same below) Performance comparison chart under the same gas flow rate conditions, investigating the effect of different catalysts on methane conversion rate. The results show that the highest methane conversion efficiency of NiSiO3-Pd-F catalyst is 96%, and the highest methane conversion efficiency of NiSiO3-Pd-A catalyst after aging treatment is 82%. Figure 1 It was found that the conversion rate of NiSiO3-Pd-F catalyst was close to that of SiO2-Pd-F catalyst, but the curve was slightly slower, indicating that although the NiSiO3 carrier improved the dispersibility of Pd, the surface flake structure led to limited gas diffusion during the reaction, resulting in a slightly lower overall reaction rate. The performance of NiSiO3-Pd-A catalyst decreased, which was higher than that of SiO2-Pd-A, especially under high temperature aging (850℃ / 25 hours), the surface needle structure can effectively inhibit the agglomeration of Pd. This shows that the NiSiO3 carrier plays an important role in maintaining the thermal stability and activity of Pd. The methane conversion rate of SiO2-NiO-Pd-F catalyst can reach 100%, and the methane conversion rate of SiO2-NiO-Pd-A catalyst after aging can still reach 98%. The conversion rate of SiO2-NiO-Pd-F catalyst is high, and the curve is very steep (fast conversion rate), indicating that the introduction method of NiO can significantly affect the activity of Pd. The interfacial interaction between NiO and Pd increases the number of catalytic active sites and optimizes the gas diffusion path. The SiO2-NiO-Pd-A catalyst exhibits the best high temperature stability, T 50 and T 90 The catalyst performance varies due to the different methods of adding Ni. The reason is that in the SiO2-NiO-Pd catalyst prepared by the impregnation method, Ni mainly exists in the form of NiO and NiO2, which is manifested as an obvious NiO diffraction peak (such as XRD Fig.12 ). Due to the hydrothermal method, a NiSiO3 hollow structure composite phase was generated. This morphology is formed because Ni reacts with SiO2 under hydrothermal conditions to generate nickel silicate (NiSiO3). XRD Fig.12 This indicates that Ni exists mainly in the form of nickel silicate. In the impregnation method, Ni is directly deposited on the SiO2 surface without undergoing significant crystal reorganization and structural evolution. Therefore, Ni mainly appears as an oxidized unit, and the form of Ni plays an important role in the performance of the catalyst. NiO can be evenly distributed on the SiO2 surface, which can increase the interaction with the active phase of PdO. At the same time, the presence of SiO2 helps to improve the stability of nickel and prevent Ni from agglomerating or losing during the reaction, which allows the SiO2-NiO-Pd catalyst to maintain a good structure and catalytic performance under high temperature conditions of methane combustion.

[0113] 2. Effect of gas flow rate on catalyst methane conversion rate

[0114] 0.5 g of the catalyst prepared in Example 1 and Comparative Example 2 were placed in the constant temperature zone of the fixed bed reactor quartz tube, fixed on both sides with quartz wool, and heated by an electric furnace. The reaction gas was introduced in the above manner, with a specific composition of 5000 ppm CH4, 6000 ppm O2, and N2 as the balance gas, with a total gas flow rate of 40000, 60000, and 80000 mL·min, respectively. -1 ·g -1 The reaction temperature was controlled to be in the range of 100-550°C. The gas composition and content were detected online using the American Andover MKS multi-gas series FTIR gas analyzer.

[0115] Fig.10 The results are as follows: the different catalysts in Example 1 and Comparative Example 2 under the same conditions and different gas flow rates (40000 mL·min -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 ) performance comparison chart, and investigated the effect of different gas flow rates on the methane conversion rate of the catalyst. The results showed that the gas flow rate had a great influence on the performance of the NiSiO3-Pd catalyst, and the ignition temperature increased with the increase of gas flow rate (40000mL·min -1 ·g -1 <60000mL·min -1 ·g -1 <80000mL·min -1 ·g -1). This shows that as the gas flow rate increases, the contact time between methane and the catalyst surface shortens, which is not conducive to the methane oxidation reaction at low temperatures. The gas flow rate has little effect on the performance of the SiO2-NiO-Pd-F catalyst with strong catalytic activity. Although the ignition temperature also increases slightly with the increase in flow rate, the overall ignition temperature is significantly lower than that of the NiSiO3-Pd-F catalyst. The methane conversion rate of the SiO2-NiO-Pd-F catalyst is 40000mL·min at different gas flow rates. -1 ·g -1 、60000mL·min -1 ·g -1 、80000mL·min -1 ·g -1 The conversion rate of NiSiO3-Pd-F catalyst can reach 100%, which is due to the uniform distribution of NiO layer, which significantly enhances the activity and stability of Pd and maintains high catalytic performance at high flow rate. Although the NiSiO3-Pd-F catalyst is not as dependent on the space velocity as the NiO2-NiO-Pd-F catalyst, it still has a high conversion rate under low space velocity conditions (4W), indicating that its NiSiO3 structure can provide sufficient active sites at a longer residence time. 50 and T 90 It increases slightly with the increase of air velocity, but the amplitude is small, especially under the conditions of 6W and 8W, the conversion rate remains almost unchanged, indicating that the catalyst is less sensitive to changes in air velocity than the SiO2-Pd-F catalyst. The hollow sphere structure of the NiSiO3 carrier provides a large specific surface area, and the surface has a lamellar and needle-like structure, forming a stable physical barrier to inhibit the migration and sintering of Pd. Although the catalytic activity of the NiSiO3-Pd series is slightly lower than that of the SiO2-NiO-Pd series, its inhibitory effect on Pd sintering is still significant. This result shows that the reasonable design of the catalyst carrier (introduction of Ni) can effectively improve the adaptability and high-temperature stability of the catalyst at different gas flow rates, providing an important reference for the practical industrial application of methane catalytic oxidation.

[0116] 3. Catalyst structure and stability characterization

[0117] 1) The NiSiO3-Pd catalyst prepared in Comparative Example 2 was characterized. Fig.11The TEM and EDX images of NiSiO3-Pd catalysts show that the TEM results of NiSiO3-Pd-F catalysts show that the hollow spherical structure remains intact, but the morphology of the hollow spheres shrinks, but the complete hollow structure is still maintained. The surface morphology of NiO is flaky (compared with the carrier, the structure changes), and the flaky structure is formed due to surface diffusion. This flaky structure may be an intermediate state formed by NiO in the initial heat treatment (short time and low temperature) to reduce energy. The EDX results show that the Pd particles of the NiSiO3-Pd-F catalyst are more evenly dispersed and the particle distribution is fine, indicating that the pore structure of the NiSiO3 hollow spheres effectively inhibits the aggregation of Pd particles at high temperatures. The TEM image of the NiSiO3-Pd-A catalyst shows that the hollow spheres shrink further, and the flaky structure is further transformed into a needle-like structure. At higher temperatures, the surface energy of NiO particles is further reduced, resulting in intensified crystal growth and recrystallization. High temperature promotes the expansion of the crystal surface, and the grains grow preferentially along a specific direction. The surface forms a needle-like or nanorod morphology, and the hollow structure shrinks further. EDX results show that the Pd particles of NiSiO3-Pd-A catalyst still maintain good dispersion, and no obvious particle sintering or aggregation is observed. The high specific surface area and excellent surface structure of NiSiO3-Pd catalyst are conducive to the dispersion of Pd.

[0118] 2) The SiO2-NiO-Pd catalyst prepared in Example 1 and the NiSiO3-Pd catalyst prepared in Comparative Example 2 were characterized. Fig.12 a in the figure is the XRD curve of SiO2-NiO-Pd catalyst. The diffraction peak intensity of PdO crystals in SiO2-NiO-Pd-F catalyst is weak, indicating that the Pd particles are less crystalline, smaller in size and better in dispersion. The Pd diffraction peak of SiO2-NiO-Pd-A catalyst is significantly enhanced, accompanied by a slight shift in the peak position, which may be related to the increase in Pd particle size and the release of surface stress. The NiO diffraction peak is still clear in the aged state, indicating that NiO has good thermal stability at high temperatures and may play a role in physical isolation and chemical anchoring of Pd particles. Fig.12b is the XRD curve of NiSiO3-Pd catalyst. NiSiO3 carrier uses SiO2 as template. Under hydrothermal reaction conditions, Ni(OH)2 is uniformly deposited on the SiO2 template and gradually forms a hollow sphere structure. NiSiO3-Pd-F catalyst is dehydrated and decomposed into NiO (PDF89-7101) after heat treatment at 550℃ / 3h. Dehydration is accompanied by lattice rearrangement, resulting in enhanced crystallinity. NiO peak is sharp and has high intensity, which indicates that the crystallinity of NiO phase is high at this time. NiO (PDF78-0643) of NiSiO3-Pd-A catalyst after heat treatment at 850℃ / 3h still maintains hexagonal structure. High temperature promotes the generation of oxygen vacancies, resulting in increased lattice stress, grain rearrangement, surface defect generation and particle agglomeration. NiO peak intensity is weakened and broadened, indicating that crystal size is reduced and crystallinity is reduced. However, the crystal structure of NiO (PDF78-0643) has more crystal defects and oxygen vacancies than (PDF89-7101), which may cause adverse changes in the electronic structure of the Pd active center. The stability of the lattice decreases, the SMSI intensity weakens, and the catalytic performance of Pd is affected.

[0119] 3) The NiSiO3-Pd catalyst prepared in Comparative Example 2 was characterized. Fig.13 Thermogravimetric curve of NiSiO3-Pd catalyst. It can be seen that there is no obvious fluctuation in the black and red curves, indicating that the catalyst has no obvious mass loss fluctuation during the entire heating process. NiSiO3-Pd catalyst shows excellent thermal stability under heating conditions.

[0120] As can be seen from the above results, the present invention successfully prepared SiO2-NiO-Pd catalyst doped with transition metal Ni by impregnation method and NiSiO3-Pd catalyst doped with transition metal Ni by hydrothermal method. The introduction of NiO not only enhances the generation of active oxygen species through oxygen vacancies, but also further improves the dispersibility and reactivity of Pd by utilizing the metal-support interaction (SMSI) between Ni and Pd. In addition, the NiO layer anchors the Pd particles to prevent them from migrating and agglomerating at high temperatures. Compared with the SiO2-Pd catalyst without Ni doping, the anchoring effect of Pd is enhanced by doping Ni metal, and the interface design of the support (hollow nickel silicate nanospheres) is optimized to prevent Pd from agglomerating. The element doping strategy of this study significantly improves the methane conversion rate. The high temperature stability, catalytic activity and space velocity dependence of the prepared SiO2-NiO-Pd catalyst and NiSiO3-Pd catalyst are significantly improved.

[0121] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high temperature stable catalyst, characterized in that: The following steps are involved: Taking SiO2 nanospheres as the matrix, transition metal Ni is introduced by impregnation method to form a core-shell structure composite carrier SiO2-NiO with a thin layer of NiO uniformly covered on the surface; then Pd is loaded on the composite carrier SiO2-NiO by impregnation method to obtain a loaded palladium-based catalyst SiO2-NiO-Pd, that is, a high-temperature stable catalyst.

2. The method for preparing a high temperature stable catalyst according to claim 1, characterized in that: The specific preparation steps of the SiO2 nanospheres include: mixing ammonia water, anhydrous ethanol and deionized water, stirring, adding tetraethyl orthosilicate, continuing stirring, centrifuging, and drying to obtain SiO2 nanospheres; Wherein, the volume ratio of the ammonia water, anhydrous ethanol, deionized water and tetraethyl orthosilicate is (200-250):(200-250):(10-20):(20-30).

3. The method for preparing a high temperature stable catalyst according to claim 1, characterized in that: The specific preparation steps of the composite carrier SiO2-NiO include: mixing SiO2 nanospheres with deionized water, adding a nickel source, adjusting the pH to 6-7, and stirring until the water evaporates to obtain the composite carrier SiO2-NiO; Wherein, the dosage ratio of the SiO2 nanospheres to deionized water is (100-110) g: 250 mL; The mass ratio of the SiO2 nanospheres to the nickel source is (100-110):(10-11), and the nickel source is nickel acetate.

4. The method for preparing a high temperature stable catalyst according to claim 1, characterized in that: The SiO2-NiO-Pd includes fresh SiO2-NiO-Pd-F and aged SiO2-NiO-Pd-A.

5. The method for preparing a high temperature stable catalyst according to claim 4, characterized in that: The specific preparation steps of the fresh SiO2-NiO-Pd-F include: mixing the composite carrier SiO2-NiO with deionized water, stirring, adding a palladium source, adjusting the pH to 5-6, stirring until the water evaporates and then drying, and calcining at a first temperature to obtain fresh SiO2-NiO-Pd-F; The specific preparation steps of the aged SiO2-NiO-Pd-A include: continuing to calcine the fresh SiO2-NiO-Pd-F at a second temperature to obtain aged SiO2-NiO-Pd-A; the second temperature is 180-320°C higher than the first temperature.

6. The method for preparing a high temperature stable catalyst according to claim 5, characterized in that: The amount of the palladium source added is 1% of the mass of the composite carrier SiO2-NiO; and / or The drying conditions are: drying at 100-120°C for 12 hours; and / or The conditions for calcining at the first temperature are: calcining at 550-570° C. for 3 h; and / or The conditions for continuing calcination at the second temperature are: calcining at 850-870° C. for 25 hours.

7. A high temperature stable catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the high temperature stable catalyst as claimed in claim 7 in the complete oxidation reaction of CH4.

9. Use of the high temperature stable catalyst as claimed in claim 7 in an efficient catalytic system in the field of clean energy.

Citation Information

Patent Citations

  • Bimetal methanation catalyst and preparation method thereof

    CN101703933A